Estudio del efecto del uso de anticuerpos contra el virus de la leucosis bovina como suplemento dietario en terneros - Porta, Natalia Gabriela (2019)
In this work we studied the effect of the use of anti-BLV specific egg yolk antibodies (IgY) as a supplement in the milk of calves during the whole breeding period, monitoring the animals from birth to 9 months of age. The main objective was to obtain evidence that milk consumption could be a route of transmission of the virus and if so, to propose an alternative to interfere with the natural challenge of BLV infection due to milk\nconsumption. As a complementary objective, experimental infections were carried out in sheep in\nwhich the minimum infectious dose was determined both of FLK-BLV cell-associated virus and of free virus in FLK-BLV cell supernatant. The neutralizing capacity of the\nantibodies present in the serum of an animal infected with BLV was also analyzed. It should be noted that prior to the use of animals an attempt was made to develop an in vitro assay.\nThe characterization of the herd where the experience with calves was developed was carried out. An individual antibody prevalence of 96% was observed in blood samples\nand 90% in milk samples. The antibody titers in blood were significantly higher than those found in milk. The presence of provirus was detected in 82% of the blood samples and\n59% of the individual milk samples. The proviral load in milk was significantly lower than in blood. In the milk of the milking tank, antibodies were found with a titer of 1:32 in all the samples, whereas in the samples of individual milks the range of antibody titers varied between <1:16 and> 1:64. When comparing the individual milks with a titer of 1:32 with the tank milks that possess the same title, it could be observed that 90% of the tank milks show detectable proviral loads, while only 60% of those individual milks evidence\ndetectable proviral load. Anti-BLV antibodies were detected in 95.5% of the newborn calves, showing a correct colostrum intake, where 13% of the calves were born infected\n(detection of provirus in blood). In the sheep bioassay, it was observed that 5,000 FLK-BLV cells were enough to\ngenerate the infection in the two lambs inoculated, while the free virus in FLK-BLV cell supernatant was infective until dilution 1/1000. BLV-positive bovine serum prevented\ninfection in lambs inoculated with cell-free virus, whereas all sheep were infected when inoculated with cell-free virus in the presence of BLV-negative bovine serum.\nThe necessary amount of an egg powder with specific anti-BLV antibodies was produced for the controlled field efficacy test. The preparation was characterized by ELISA and by experimental infection in lambs. All lambs were infected when they were inoculated with 7FLK-BLV cell-free virus previously incubated with the concentrated anti-BLV IgY\npreparation and with the BLV egg powde, not demonstrating the ability of the anti-BLV IgY to neutralize the virus present in the supernatant of FLK-BLV cells. Although the in\nvivo test was an alternative for the in vitro test in order to analyze the neutralizing capacity of the IgYs antibodies, and although the expected results were not obtained, it has been\nbeneficial for the group, as a new and valid tool to carry out different studies.\nThis powder was supplied to the calves in each milk intake during breeding. In parallel in a control group, no supplement was offered in the daily milk intakes. In the first days of life of the calves, 93% of the samples contained antibodies both in the control group and in the treated group. These values agree with what was previously reported for\ninfections in newborn calves. The following samplings were carried out until the 9-month follow-up of the calves was completed, where a prevalence of 6.6% and 7.7% was observed in the treated and in the control group, respectively. This thesis provided data on the natural epidemiology of the infection, which should be\nused to design and pursue a control strategy. In a context of endemic natural infection,\nthe strategy of using antibodies as an adjunct in the daily milk intake could be valuable for the reduction of the dynamics in the early age.